A MODEL FOR THE COMBINED EFFECTS OF STRESS RATIO AND GRAIN SIZE ON THE LEFM FATIGUE THRESHOLD CONDITION - Lal D.N. (My University, 2025)
A long‐crack, fatigue‐threshold model which explains and predicts the commonly observed effects of stress ratio, R, and grain size, d, on δK0, is proposed. The inclusion of a grain‐size‐effect is an extension of a recently proposed model that examined the effect of the R ratio. The extended model is based on the hypothesis that near‐threshold, crack growth involves two micro‐mechanical processes of fracture; Kmax‐controlled submicroscopic cleavage, which predominates when the defect concentration is small, and δK‐controlled reversed shear which predominates when the defect concentration is large, both processes occurring in a critically stressed volume, Vc, ahead of the crack tip. Defect concentration in Vc is reduced by a low value of R and a coarse grain size and is increased by a high value of R and a fine grain size. Good agreement is shown to exist between predicted and experimental curves of δK0 versus R and δK0 versus grain size for several steels and aluminium alloys. In particular, δK0 is shown to have an upper and a lower bound value for a material. The model may be used as an alternative procedure for obtaining quick, approximate but conservative estimates of δK0 for practical design applications. Copyright © 1992, Wiley Blackwell. All rights reserved